PERANCANGAN STRUKTUR DINDING PENAHAN TANAH PADA PEKERJAAN PENANGANAN LONGSORAN JALAN BATU CERMIN KOTA SAMARINDA - IDI, JUMA (KURVA S JURNAL MAHASISWA, 2018)
Landslide are one of the natural disasters that often occur in Indonesia. This is due to geological conditions and processes such as faults, earthquakes, and volcanic activity which continue to this day. Landslide that occurred on the batu cermin road segment due to rainwater infiltrating into the ground in open slope (without vegetation cover) cause the water content in the soil to increase The retaining wall is a structure is design and built to withstand lateral soil stress caused by backfill material.The stability of retaining wall is of obtained mainly from its weight and the weight of the soil at the toe and the heel of retaining wall. The method used in analyzing the stability of retaining wall in the type of counterfort & type buttress is by using Coulomb and Rankine methods, while the method used in analyzing the carrying capacity of the soil occurring using Terzaghi method. From the calculation results can be concluded that, the stability of the retaining wall in the type of counterfort & buttress type was safe against the stability of the rolling force and the stability of the bearing capacity of the soil, but the stability of the shear force was not sufficient so that the necessary foundation piles to strengthen the structure of the retaining wall .